1222 Improving Consenting for Emergency General Surgery During The COVID-19 Pandemic. (12th October 2021) - Oyewole, B; Sandhya, A; Tawfik, A; Elzaafarany, A; Ma, J; Jethwa, P
Abstract: Aim: Patients undergoing surgery during the Covid pandemic are exposed to increased risks of pulmonary complications and mortality. These novel risks need to be documented on the consent form. We carried out various interventions to ensure appropriate consenting and documentation following an initial audit that revealed poor compliance with published guidelines. Method: The initial audit reviewed consent forms of patients undergoing emergency surgery over two-weeks in May 2020 while the re-audit was over a two-week period in June 2020 following implementation of interventions. Inclusion Criteria: Age >18-years, urgent or emergency laparoscopic surgery Exclusion criteria: Age <18-years, Open surgery, 'Covid-light' areas, NELA. Results: 57 consent forms were assessed during the audit loop: 22 laparoscopic appendicectomies and diagnostic laparoscopies, 14 incision and drainage, 8 laparoscopic cholecystectomies, 4 hernia repairs, and 9 other procedures. Consenting for covid pneumonia increased from 70% to 89%, potential ITU admission 56% from 25% and the risk of death 63% from 21% Conclusions: The covid pandemic changed our surgical practice. There are many unknowns regarding the risks to surgical patients, however, evidence shows increased risks of covid pneumonia, ITU admission and death in the perioperative period. Our consenting and the documentation of such conversations with patients must reflect our new reality.